Using Mobile Health Based Expert System In Monitoring Risk Signs Of Pregnancy: Literature Review: Penggunaan Mobile Health (mHealth) Berbasis Sistem Pakar Pada Pemantauan Tanda Bahaya Kehamilan: Literature Review - Pindi Kurniawati; Sukihananto; Dinny Atin Amanah (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
The maternal mortality rate is still quite high. Pregnant women need to understand the danger signs of pregnancy toprevent emergencies. Health workers can also carry out early detection of danger signs of pregnancy in mothers.Currently, pregnancy monitoring is being carried out by mothers independently with an expert-based mobile healthapplication. Expert-based mHealth is one of the efforts that can be made to monitor pregnancy. The aimed of thisliterature study is to determine the effectiveness of using expert system-based mHealth in pregnancy monitoring. Method: writing in this study used the PRISMA method to describe the application of expert system-based mHealth in pregnancy monitoring. Scientific articles were collected from an online database consisting of ClinikalKey Nursing, Elsevier,Scholar, and Scopus from 2017 to 2022. Results: the use of an expert system-based mHealth application has proveneffective in improving pregnancy monitoring, especially in monitoring pregnancy danger signs so that it can be carriedout early warning of high risk pregnancy. In conclusion, this application is useful for pregnant women and health workers.This application is needed by mothers and health workers in monitoring their pregnancy effectively, easily and costeffectively. Recommendation: it needs to be integrated with health services, both puskesmas and hospitals.